Forgotten/retained double J ureteric stents: A source of severe morbidity in children - Rajendra B Nerli; Prasad V Magdum; Vikas Sharma; Ajay Kumar Guntaka; Murigendra B Hiremath; Shridhar Ghagane (Wolters Kluwer Medknow Publications, 2016)
Background: The increase in the usage of double J (DJ) ureteral stents in the management of a variety of urinary tract disease processes mandates familiarity with these devices, their consequences and their potential complications, which at times can be devastating. We retrospectively reviewed our series of children with forgotten/retained DJ ureteric stents. Materials and Methods: Hospital records of all patients' <18 years old who underwent removal of forgotten/retained DJ ureteral stent at our hospital were reviewed for age, gender, indication for insertion of DJ stent, duration of stent insertion, radiological images and surgical procedures performed. Results: During the study period, January 2000 to December 2014 (a 15-year period), a total of 14 children underwent removal of forgotten/retained DJ ureteral stent. A combination of extracorporeal shock wave lithotripsy, cystolitholapaxy and percutaneous nephrolithotomy was done to free the DJ stent and extract it. Conclusions: Forgotten/retained stents in children are a source of severe morbidity, additional/unnecessary hospitalisation and definitely financial strain.